Implementation and evaluation of service learning at higher education institutions - Schultes, Marie-Therese; Graf, Daniel; Holzer, Julia; Schober, Barbara; Spiel, Christiane (Pergamon Press, 2026)
Service learning courses enable students and lecturers at higher education institutions to take on social responsibility by collaborating with community partners. In this literature review that is complemented by empirical examples, we present advantages and challenges of this teaching approach as well as guidelines for developing concepts for a university-wide implementation and evaluation of service learning. Our article is informed by higher education, implementation and evaluation research and findings from the Third Mission project of the University of Vienna, Austria. Within the scope of the project, we conducted a multi-stakeholder workshop and an interview study with representatives from seven universities. We illustrate the service learning approach with two course examples from the University of Vienna’s psychology master’s programme. Then, we discuss how service learning can be systematically implemented at the university level using frameworks from implementation science and findings from an interview study. Results indicate that successful implementation of service learning at the university level is supported by long-term collaboration between the university and community partners and an institutional culture that visibly values students’ and lecturers’ additional efforts. Finally, we seek to advance the evaluation of higher education by presenting a comprehensive participatory approach to service learning assessment that actively involves diverse stakeholders, including students, faculty, and community partners and that can be applied across various disciplines. By integrating multiple perspectives, we offer a framework for capturing the multidimensional impacts of service learning on educational outcomes and community engagement.